Peran Pelatihan Kewirausahaan pada Motivasi dan Keterampilan Mahasiswa Jurusan Ekonomi Islam Fakultas Syariah dan Ekonomi Islam IAIN Pontianak - Ariza, Anggatia (Fakultas Ekonomi dan Bisnis, UNTAN, 2018)
Unemployment is considered as one of the problems happened in developing countries. One of the efforts to overcome this problem is to accelerate the number of entrepreneurs. Furthermore, this research aims to perceive the roles of the entrepreneurs training on the entrepreneurship motivation and skill of Islamic Economics students at IAIN Pontianak. This research would be written by using action research. Besides, the data would be collected by interviewing, and observation. Then, the triangular method would be performed on the Chief of Islamic Economics Department to verify the real data. Moreover, the roles of entrepreneurship training on the entrepreneurship motivation are, mostly, students of Islamic Economics Department feel the growing of enthusiasm, the students' bravery to face the risks, and their self-esteem would be better. The roles of entrepreneurship training on the entrepreneurship skills are the creativity and innovation of students could be more developed. Then, it also could help the students to solve the problems in a better way on communication, leadership, strategy planning, and time balancing between study and business.